Composition and Arrangement Style of Modern Gospel Music: A Musicological Study of the Song "Kunaikkan Syukurku" by NDC Worship - Mathias Diasmara Arfeni; Irfanda Rizki Harmono Sejati (Repertoar, 2026)
Modern gospel music in Indonesia is growing rapidly, alongside the increasing production of contemporary worship works that meet high musical standards. NDC Worship's song "Kunaikkan Syukurku" has been viewed more than 17 million times on YouTube and listened to more than 12 million times on Spotify. However, no systematic academic study has examined its composition and arrangement. This study aims to describe the compositional technique and analyze the characteristics of the modern gospel music arrangement in the song, especially in the Reimagined version. The method used is a qualitative descriptive analysis approach grounded in musicology, using auditory transcription, score observation, document study, and practitioner interviews, with source triangulation as a data validity technique. The results showed that this song was built on the form of two parts (A–B) with 19 beats, developed through sequencing techniques, literal repetition, and interval enlargement, and dominated by deceptive cadence and intense syncopation. The Reimagined version evolved into an 11-part structure with extended chords, a brass section, call-and-response, and harmonic flexibility typical of modern gospel. The research concludes that modern gospel identity is embedded from the basic compositional stage to the final arrangement layer, and that the arrangement's creativity extends beyond the written record.